1999
DOI: 10.1177/0148607199023004222
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Contamination of Total Parenteral Nutrition. 1. Contribution of Component Solutions

Abstract: All eight components tested were contaminated with trace elements not intended to be present in the product, and similarly, the multi-trace element component contained trace elements either above or below that which the label claimed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 15 publications
9
82
2
1
Order By: Relevance
“…The boron content of GCW as determined by us (28 lM/L) is in line with the physiologic boron plasma levels of <30 lM/L [9]. A study from the United States found 80 lM/L of TPN [10]. Berner et al reported widely varying boron contents in various parenteral fluids; the estimated concentration in a typical TPN intake was 6 lM/L [11].…”
Section: Minor Elements (Lm/l)supporting
confidence: 76%
“…The boron content of GCW as determined by us (28 lM/L) is in line with the physiologic boron plasma levels of <30 lM/L [9]. A study from the United States found 80 lM/L of TPN [10]. Berner et al reported widely varying boron contents in various parenteral fluids; the estimated concentration in a typical TPN intake was 6 lM/L [11].…”
Section: Minor Elements (Lm/l)supporting
confidence: 76%
“…[89][90][91][92][93][94][95][96] Amounts of contamination can vary between manufacturers and from lot to lot within a manufacturer's product. 92,94,96 At least a dozen minerals (from arsenic to zinc) have been identified as contaminants.…”
Section: Questionmentioning
confidence: 99%
“…97,98 The trace elements chromium and zinc are the most frequently measured as contaminants in a number of PN components. 90,91,95,[99][100][101][102] This may necessitate the use of individual rather than fixeddose multi-trace element products to allow dosing flexibility for patient PN regimens when contaminants are of concern. Further research is recommended on micronutrient contamination of PN.…”
Section: Questionmentioning
confidence: 99%
“…Manganese contaminants in PN can be as high as 0.31 mg/L, with dextrose and electrolyte solutions contributing as much as 0.038 mg/L. 6,10,[30][31][32] Home PN patients have had elevated serum manganese concentrations after more than 10 years of eliminating manganese from their PN. 33 Because manganese is mostly excreted in the bile, manganese accumulation occurs in patients with cholestasis.…”
Section: Manganesementioning
confidence: 99%